Simultaneous parametric optimization for design and operation of solvent-based post-combustion carbon capture using particle swarm optimization. (5th February 2021) - Xi, Han; Liao, Peizhi; Wu, Xiao
Graphical abstract: Highlights: Optimal design of the PCC considering the load variation of upstream CFPP. Daily average CO2 capture level is applied to enlarge the optimization space. Hierarchical optimization is proposed based on PSO to search the best parameters. Design result assessment from economic, efficiency and environmental aspects. Abstract: High investment and operating costs are two barriers hindering the commercial deployment of solvent-based post combustion CO2 capture (PCC) technology in power industry. Since upstream power plants are always in flexible operation, conventional approaches which carry out the design based on a fixed condition fail to achieve the best overall performance. To this end, this paper proposes a simultaneous size and operation parameters optimization strategy for the PCC process, in which the flexible operation of the CFPP is taken into account during the design stage. The technique of particle swarm optimization (PSO) is used in a hierarchical manner to find the design and operating conditions of the PCC with minimal total annualized cost. To further explore the optimization potential, the average CO2 capture level in one day is taken as the environmental constraint rather than the conventional instantaneous one. The proposed approach is tested on the PCC design for an existing 660 MW supercritical coal-fired power plant. The optimization results of four different design approaches are compared with the economic, efficiency and environmental (3E) performance being fully assessed. The simulation results show that by using the proposed optimization method, 14.45% reduction in TAC can be attained compared with the conventional approach.